Mushroom Polysaccharides as Natural Modulators of IL-17: Implications for Gut Microbiota, Autoimmune Diseases and Cancer Therapy - Liu, Kunang; Wang, Kana; You, Zongbing (Serican Journal of Medicine, 2025)
Interleukin-17 (IL-17, also known as IL-17A) is a member of the pro-inflammatory cytokine family that plays a pivotal role in immune defense, inflammatory responses, and tissue homeostasis. It contributes to host protection, autoimmune diseases, and cancer progression. Recent studies have highlighted the critical role of gut microbiota in immune regulation and tumor progression. Alterations in its composition can disrupt protective mechanisms, increase infection risk, and elevate the likelihood of metabolic and immune-related diseases. Mushroom polysaccharides are biological macromolecules extracted from the fruiting bodies, mycelia, or fermentation broth of mushrooms. These compounds achieve anti-tumor, anti-inflammatory, anti-oxidative, and immune-regulatory effects by modulating gut microbiota, increasing short-chain fatty acid production, enhancing intestinal mucosal barrier function, regulating lipid metabolism, and activating specific signaling pathways. Mushroom polysaccharides have been shown to regulate IL-17 both directly through key signaling pathways and indirectly by modulating gut microbiota, thereby influencing immune-related diseases and tumor progression. Therefore, mushroom polysaccharides, acting as natural regulators of IL-17, possess extensive application potentials in cancer therapy and immune disease management.